Efficient synthesis of 1,3-diaryl-4-halo-1H-pyrazoles from 3-arylsydnones and 2-aryl-1,1-dihalo-1-alkenes - Yang, Yiwen; Kuang, Chunxiang; Jin, Hui; Yang, Qing; Zhang, Zhongkui (Beilstein Journal of Organic Chemistry, 2011)
An efficient synthesis of 1,3-diaryl-4-halo-1H-pyrazoles was achieved. The synthesis involves the [3 + 2] dipolar cycloaddition of 3-arylsydnones and 2-aryl-1,1-dihalo-1-alkenes. The process proceeds smoothly in moderate to excellent yields. 1,3-Diaryl-4-halo-1H-pyrazoles are found to be important intermediates that can easily be converted into 1,2,5-triaryl-substituted pyrazoles via Pd-catalyzed C–H bond activation.
Keywords: C–H bond activation; cycloaddition; dihaloalkenes; pyrazole; sydnones